Pengaruh Model Pembelajaran Contextual Teaching and Learning Terhadap Motivasi Belajar PAK dan Budi Pekerti Siswa Kelas XI SMA Negeri 2 Sibolga Tahun Pembelajaran 2023/2024 - Rifka Br Napitupulu; Goklas J. Manalu; Andrianus Nababan; Elvri T. Simbolon; Nisma Simorangkir (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The study aims to determine the positive and significant effect of the Contextual Teaching and Learning learning model on the motivation to learn PAK and Budi Pekerti of class XI SMA Negeri 2 Sibolga in the 2023/2024 Learning Year. The research hypothesis is that there is a positive and significant influence between the Contextual Teaching and Learning learning model on the motivation to learn PAK and Budi Pekerti of class XI SMA Negeri 2 Sibolga in the 2023/2024 Learning Year. Descriptive and inferential quantitative research methods. The population of all grade XI students of SMA Negeri 2 Sibolga in the 2023/2024 academic year who are Protestant Christians totaling 106 people. Random sampling is 32% of the total population, namely 34 people. The research instrument is a closed questionnaire. The results of the analysis requirements obtained the value of rxy= 0.573> rtable = 0.339 andtcount=3.955> ttable = 2.042 indicate a positive and significant relationship between the Contextual Teaching and Learning learning model with PAK and Budi Pekerti learning motivation of class XI students of SMA Negeri 2 Sibolga in the 2023/2024 Learning Year. The results of regression analysis obtained: a) regression equation. b) Determination test obtained the amount of influence, namely (r2) x100% = 32.83%. c) Hypothesis testing obtained Fhitung= 15.624> Ftabel= 3.32 then H0 is rejected andHa is accepted. The study concluded that the Contextual Teaching and Learning learning model applied by PAK teachers seriously in the teaching and learning process can increase the motivation to learn PAK and Budi Pekerti of class XI SMA Negeri 2 Sibolga in the 2023/2024 Learning Year.